Prevalence and factors associated with leisure-time physical activity: survey repeated in university students - Santos, Sueyla Ferreira Da Silva Dos; Freitas, Ismael Forte [UNESP]; Alvarenga, Ana Maria; Fonseca, Silvio Aparecido; Virtuoso, Jair Sindra; Sousa, Thiago Ferreira De (Universidade Federal de Santa Catarina, 2016)
The practice of leisure physical activity represents a behavior that must be monitored in different population groups. The objectives of this study were i) to compare the prevalence of leisure-time physical activity in university students along the survey years in three separate years; ii) to analyze the factors associated with practice of leisure-time physical activity in each survey. Three surveys in a college institution in northeastern Brazil in 2010, 2012 and 2014 were carried out. The dependent variable was practice of leisure-time physical activity. Exploratory variables were sociodemographic factors and link with the university. The prevalence was compared using the chi-square test for linear trend and association for Prevalence Ratio. Participation was of 1,084, 1,085 and 1,041 college students in 2010, 2012 and 2014, respectively. The prevalence of leisure-time physical activity was approximately 50% in the three surveys. Women were less active in leisure time on the three surveys. In each survey, associations were different in relation the courses, and Chemistry – teacher training, Computer Science, Pedagogy – teacher training and Linguistics (no specialization) students showed lower levels of leisure-time physical activity and Biomedicine, Geography – Bachelor, Physical Education – teacher training and Geography – teacher training students were more active in leisure time. It was concluded that there was a stabilization of the prevalence of active leisure over time and that women showed lower prevalence of leisure-time physical activity in the three surveys.

A prática de atividades físicas no lazer representa um comportamento que auxilia na obtenção de potenciais beneficios para a saúde. Os objetivos deste estudo foram i) comparar as prevalências de universitários ativos no lazer entre três inquéritos transvesais; ii) analisar os fatores associados à prática de atividade física no lazer, em cada inquérito. Foram realizados três inquéritos nos anos de 2010, 2012 e 2014. O desfecho deste estudo foram os ativos no lazer (≥1 dia por semana). As variáveis exploratórias foram as sociodemográficas e de vínculo com a universidade. As prevalências entre os inquéritos foram comparadas pelo teste qui-quadrado para tendência e a associação foi estimada pelas Razões de Prevalências. A participação foi de 1.084, 1.085 e 1.041 universitários nos anos de 2010, 2012 e 2014, respectivamente. As prevalências de ativos no lazer foram de aproximadamente 50% nos três inquéritos. As mulheres foram menos ativas no lazer nos três inquéritos. Os universitários vinculados aos cursos da Biomedicina, Geografia – bacharelado, Educação Física – licenciatura e Geografia – licenciatura foram associados com maiores razões de prevalências de prática de atividades físicas no lazer. Os universitários com menores razões de prevalências de prática de atividades físicas no lazer foram provenientes dos cursos de Química – licenciatura, Ciência da computação, Pedagogia e Letras (sem habilitação). Conclui-se que houve a estabilização da prevalência de universitários ativos no lazer ao longo do período de análise e que as mulheres apresentaram menores prevalências de prática de atividades físicas no lazer nos três inquéritos.
Prevalência e fatores associados à prática de atividades físicas no lazer: inquérito repetido em estudantes universitários
Keywords: Cross-sectional studies; Longitudinal studies; Recreational activities; Students; Atividades de lazer; Estudantes; Estudos longitudinais; Estudos transversais